DNA barcoding revealing mislabeling of seafood in European mass caterings. (October 2018) - Pardo, Miguel Ángel; Jiménez, Elisa; Viðarsson, Jónas R.; Ólafsson, Kristinn; Ólafsdóttir, Guðbjörg; Daníelsdóttir, Anna Kristín; Pérez-Villareal, Begoña
Abstract: Seafood is amongst the most internationally traded food commodities worldwide and it is one of the food groups most likely to be subject to fraud. A number of studies have been conducted where samples from retail-, restaurant- and food service outlets have been tested for species substitution. These studies have mostly focused on specific species, particular types of outlets or confined to some geographical location. The study presented in this paper is the first large-scale attempt to study the rate of fish mislabeling in mass caterer (HoReCa) sector across Europe. A total of 283 samples were collected in 180 mass caterer outlets in 23 European countries. DNA barcoding revealed that 26% of the samples were mislabeled and that 31% of the outlets sold mislabeled seafood. The highest mislabeling rate was observed in Spain, Iceland, Finland and Germany, where close to 50% of the outlets sampled offered mislabeled seafood. Conversely, there was no mislabeling detected in Sweden, Switzerland and Slovakia. The species with the highest mislabeling rates were dusky grouper, butterfish, pike perch, sole, bluefin tuna and yellowfin tuna. In the case of other important fish species in Europe such as hake, cod, haddock and swordfish, mislabeling rates ranged between 14 and 33%. The results of the study show that the majority of the mislabelings are with cheaper fish, such as the presence of Pangasius commonly substituting other species, being labeled as more expensive ones, suggesting economic motivation for mislabelling. Highlights: This study included 283 samples in 180 mass caterers from 23 European countries. One out of three mass caterer establishments served mislabeled meals in Europe. The highest mislabeling rate was observed in Spain, Iceland, Finland and Germany. Pangasius is the most prevalent fish species found substituting other species.